PARTISIPASI KELOMPOK TANI DALAM USAHA KONSERVASI TANAH DI DESA HUTA BARINGIN KECAMATAN PANYABUNGAN BARAT KABUPATEN MANDAILING NATAL - Hasanta, Febri; Edial, Helfia; Zahara, Leni (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information , analyze and discuss data concerning ( 1 ) Participation of Farmers Group On Time Expended In Soil Conservation Effort ( Multiple Cropping , Mulch , Soil Treatment , Drainage ) in the village of Huta district Baringin Panyabungan West Mandailing Natal ( 2 ) Knowledge Farmers Group in Land Conservation Effort ( Multiple Cropping , Mulch , Soil Treatment , Drainage ) in the village of Huta Baringin Panyabungan West Mandailing Natal Western District. Type of research that the authors use is descriptive research . Data were collected through observation , interviews , documentation . Research informants were farmers group in the village of Huta district Baringin Panyabungan Mandailing Natal Western District .This type of research is descriptive . The study population is the entire group of farmers who were 21 groups . Samples were taken by purposive sampling technique to sample totaled 12 groups based groups : the group that has the highest number of members in the top 20 .Based on the analysis of the data it can be concluded as follows : ( 1 ) Expended time given by farmer groups in implementing soil conservation efforts ( Multiple Cropping , Mulch , Soil Treatment , Drainage ) in the village of Huta district Baringin Panyabungan Mandailing Natal West District has 77.2 % percentage this includes both categories , while 22.8 % are unfavorable . ( 2 ) knowledge possessed by farmers groups in implementing soil conservation activities ( Multiple Cropping , Mulch , Soil Treatment , Drainage ) in the village of Huta district Baringin West Panyabungan Mandailing Natal regency has this percentage of 73.3 % categorized as good , while 23.6 % are less good and 2.9 % in the category are not good .